Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
Legal Tender Band playing music: Bob Fishman and John B. Smith on guitar, Hal Bolen on drums, Dave Maybary on saxophone, Ken Fransen and Robert Oliver on trumpet 5080 E. Kings Canyon Road, Fresno